Implementation of Online Learning Using the Google Platform by Islamic Religious Education Teachers in Class XI SMA Negeri 1 Seyegan - Rahmanto, Azhar; Wahidin, Imam Nur (International Journal of Social Service and Research, 2021)
The background of this research is to find out about the application of PAI teachers in online learning using features on the Google platform located at SMA Negeri 1 Seyegan. The purpose of this study was to determine the online learning process using the features on the Google Platform along with the supporting factors and inhibiting factors that existed during the implementation of PAI learning by using the features on the Google Platform in class XI Islamic Religious Education SMA Negeri 1 Seyegan. This research is a type of qualitative research with descriptive analysis techniques. This research takes the background of SMA Negeri 1 Seyegan. Data were collected through observation, interviews and documentation. The results of the study indicate that: (1) The implementation of Islamic Religious Education teachers in Online Learning using the Google Platform in Class XI SMA Negeri 1 Seyegan includes (a) learning preparation: preparing learning materials using Google Slides and Youtube media in the form of images and videos, (b) implementation of learning: learning activities using Google Classroom which include preliminary activities, core activities and closing with question and answer methods and quizzes (c) evaluation of learning: assessment of learning outcomes using Google Form in the form of quizzes and exams. (2) the factors that support online learning using the Google Platform, namely, schools facilitate wifi and computers for teachers, as well as the inhibiting factors for online learning using the Google platform, namely, the limited access of students to the internet and mobile devices